Transforming the study of religious situations: The view of post-secular society theories - S. Astapov (Acta Theologica)
This article considers the methodology of post-secular society theories for application to research on religion. Several issues of present sociological methodology are associated with the secular discourse that divides society into subsystems and represents religion as one of them. Such an approach does not consider the role of noninstitutional forms of religion, religious ideas, and moods of individuals in forming the religious situation. The discourse emerging from theories of the post-secular society, which recognise the transformation of the place of religion in the public sphere at the beginning of the 21st century, views the contradictory unity of religious and secular moments in any social phenomenon. This transforms the established scientific approach to the study of religion with concepts of post-secular society theories. This article defines the principal characteristics of the post-secular model of religious situations compared to the principles of the secular model.